2009
DOI: 10.1186/bcr2257
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA signatures predict oestrogen receptor, progesterone receptor and HER2/neureceptor status in breast cancer

Abstract: Introduction Breast cancer is a heterogeneous disease encompassing a number of phenotypically diverse tumours. Expression levels of the oestrogen, progesterone and HER2/ neu receptors which characterize clinically distinct breast tumours have been shown to change during disease progression and in response to systemic therapies. Mi(cro)RNAs play critical roles in diverse biological processes and are aberrantly expressed in several human neoplasms including breast cancer, where they function as regulators of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
299
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(319 citation statements)
references
References 59 publications
(63 reference statements)
16
299
1
3
Order By: Relevance
“…In addition, miR-342 was expressed most strongly in the ER-positive/HER2-positive tumors. 34 MiR-342 influences the ER expression level and the response to tamoxifen. 35,36 MiR-10b, miR-26a and miR-153 have been suggested to be potential biomarkers of triple-negative breast cancer (TNBC).…”
Section: Mirna and Intrinsic Subtypes Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, miR-342 was expressed most strongly in the ER-positive/HER2-positive tumors. 34 MiR-342 influences the ER expression level and the response to tamoxifen. 35,36 MiR-10b, miR-26a and miR-153 have been suggested to be potential biomarkers of triple-negative breast cancer (TNBC).…”
Section: Mirna and Intrinsic Subtypes Of Breast Cancermentioning
confidence: 99%
“…FinlaySchultz et al 40 suggested a mechanism by which the progesteronetriggered loss of miR-141 facilitates breast cancer cell de-differentiation through the deregulation of PgR and Stat5a. Furthermore, Lowery et al 34 revealed that four miRNAs (miR-520g, miR-377, miR-527-518a and miR-520f-520c) have the ability to predict PgR status with great accuracy in breast cancer. MiR-29 and miR-513a-5p also influence PgR expression in breast cancer.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…More important than its feasibility, recent advances have implicated the role of miRNA as oncogenes or tumor suppressor genes in tumorigenesis, metastasis, and response to treatment in various cancer types including breast cancer. [18][19][20][21][22][23][24][25][26][27] Although the number of miRNAs identified is relatively small (∼2588 human mature miRNAs from 1881 precusor miRNA genes reported in miRBASEv.21; www.mirbase.org), individual miRNAs can target multiple genes, and it is thought that collectively they can target approximately onethird of the human genes. 28 Thus, they act as global regulators and may be suitable diagnostic markers and therapeutic targets for inflammatory breast cancer.…”
mentioning
confidence: 99%
“…In the literature, there is a paucity of data of associations among these particular miRNAs with receptor subtypes. Lowery et al (2008) have demonstrated an association between miRNA-190 expression and ER status, but these studies were conducted on 29 early breast cancer specimens, in contrast to our own study examining more advanced stages of the disease. Lowery et al (2008) showed using artificial neural network analysis that miRNA signatures were associated with ER, PR, and HER2 status.…”
Section: Resultsmentioning
confidence: 40%
“…These particular miRNAs were selected on the basis of previous reports in the literature, the miRNA database, and communications from breast cancer conferences. They represent a broad range of epigenetic pathways involved in migration, invasion, receptor status, epithelialto-mesenchymal transition, cancer dormancy, switch to the fast growing phenotype, drug resistance, etc (Blenkiron et al, 2007;Lowery et al, 2008;Fang et al, 2012;Liu et al, 2012;Manavalan et al, 2013;Lehmann, 2014;Li et al, 2014;McDermott et al, 2014;www.mirbase.org). We also used unpublished data of TaqMan Low Density Arrays from our previous research.…”
Section: Mirna Expressionmentioning
confidence: 99%